Analisis Hukum Terhadap Pemutusan Hubungan Kerja (PHK) Di Indonesia - Zahra, Maysanda Rahmanisa; Ardiyanti, Dinita; Adnan, Muhammad Rifki; An Naufal, Yazid (UNIVERSITAS SERAMBI MEKKAH, 2025)
Termination of Employment (PHK) is the ending of the working relationship between employees/laborers and employers due to certain circumstances, resulting in the cessation of rights and obligations between both parties. In Indonesia, PHK is regulated under Law No. 13 of 2003 on Manpower and Law No. 11 of 2020 on Job Creation, along with its implementing regulations. Normatively, there are two types of PHK: voluntary PHK and involuntary PHK. PHK is a critical issue in Indonesian labor law because it directly impacts workers' fundamental rights and the stability of industries. A PHK process that is not in compliance with legal procedures can lead to significant social and economic consequences, both for workers who lose their jobs and for employers who must reduce their workforce. Additionally, PHK that is not carried out in accordance with regulations can erode public trust in the labor market and damage relationships between employers and workers. Workers affected by PHK are entitled to various rights, including compensation in the form of severance pay, long-service bonuses, and other rights as stipulated by regulations. These rights are designed to protect workers during the transition period after losing their jobs and ensure they are not financially harmed due to an unfair PHK process. Therefore, it is crucial for all parties involved to understand and adhere to the applicable legal provisions in every PHK process to ensure fairness, protect workers' rights, and maintain labor stability in Indonesia.